Technology Evolution Effect on SME Business Opportunities in Kota Bharu with Relation to Financial Business Growth - Yi Ping, Yep (2018)
This research paper is about the approaches of technology evolution effects on business opportunities development among SME Business in Kota Bharu with relation to financial business growth. Small-and-medium enterprise (hereafter known as SME) in this study mainly focuses on Malaysian small-and-medium business manufacturing firms in Kota Bharu, Kelantan. To bring this discussion into perspective, this paper adopts qualitative research for analysing technology evolution among SME business strategies, business opportunities and financial business growth support. The paper also included business and financial support from Malaysia Government-Linked agencies which are SME Corporation (hereafter known as SME Corp.) and Malaysian Investment Development Fund (hereafter known as MIDF). This study emphases on the business entities in Kota Bharu, Kelantan preferably that invest in technology manufacturing business. The adoption of technology evolution for SME business has changed dramatically over the last decades which technology evolution has become a crucial endogenous variable in aggregate production function. The new technology investments brought with high productivity rates and rapid, positive economic growth. The inter-relation between technological evolution and financial business growth effectively achieve future generation product with current technology innovation.